(untitled) (Vietnam Journal of Community Medicine, 2025)
Objectives: A survey of the clinical characteristics, paraclinical findings, microbial agents, complications, and the treatment outcomes of the lobar pneumonia at the Respiratory Department 1 in Children’s Hospital 2. Method: A prospective case series report study. Results: One hundred- thirty one (131) patients were described.The median age of onset was 5 years. Among the patients with globar pneumonia, 96.9 % had completed the full Hib vaccination schedulem, while 71% had not completed the pneumococcal vaccination. Most patients had normal white blood cell counts and neutrophil percentages in peripheral blood for their age. Elevated CRP levels (>20mg/dl) were found in 61.8% of globar pneumonia cases. On chest X-rays, right lower lobe pneumonia was the most commonly observed. The bacterial causes of globar pneumonia isolated through nasopharyngeal cultures had a low positive rate of 12.2%, with S. aureus being the most commonly identified organism. Other bacteria included H. influenzae and S. pneumoniae. Complications were present in 15.3% of globar pneumoniaa cases, most commonly respiratory failure and sepsis, followed by lung consolidation, pleural empyema and necrosis. A total of 60.5% of cases responded to initial antibiotic treatment, while 39.5% did not respond and required either a change or addition of antibiotics. Among these, Levofloxacin was the most frequently substituted antibiotic (62.2%), which correlated with a 66.4% positive rate for IgM serology diagnostic for Mycoplasma pneumoniae. Conclusion: Lobar pneumonia is a condition that can cause severe complications, with the leading bacterial pathogens being Staphylococcus aureus and Streptococcus pneumoniae. Therefore, initial antibiotic treatment for lobar pneumonia should cover both of these pathogens.